Sexual Stigma Pada Perempuan Lesbian Femme Dewasa Muda - Terutung, Beata Carmen; Sukmaningrum, Evi (ANIMA Indonesian Psychological Journal, 2024)
This study examines the unique and subjective experience of sexual stigma among sexual minority women. In Indonesia, lesbian women as a homosexual group experience more stigma and discrimination, affecting multiple aspects of life, including psychosocial, economic, legal, and health. The aim of this study is to obtain an in-depth understanding on sexual stigma experience of young adult femme lesbian women, manifested in three forms: (1) enacted sexual stigma; (2) felt sexual stigma; and (3) internalized sexual stigma. The qualitative study method with descriptive phenomenology approach utilizing in-depth interview was conducted to three participants who self-referred as femme lesbian women, with the age range of 19-30 years old. Study results found that the study participants experienced sexual stigma early on their development of sexual identity. Internalized sexual stigma was formed when the study participants were negatively exposed to enacted sexual stigma and felt sexual stigma. The impact of sexual stigma was reflected through drawbacks in the development of sexual identity, expression of social relations, and romantic relationships with lesbian women partners, as well as negative emotional well-being.